Formation of Optimal Portfolio Using Single Index Model in Investment Decisions - Joni Hendra; Khusnik Hudzafidah; Siti Chamdanah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The objective to be achieved in this study is to analyze the extent to which the return and risk of the optimal portfolio that is formed provides better performance than the return and risk of individual stocks. While the data needed to support this analysis are in the form of stock price data, the Composite Stock Price Index, and Bank Indonesia Certificates. The samples selected in this study were 34 companies based on sampling techniques, namely using sampling techniques purposive, means choosing a sample from a set of populations based on certain considerations or criteria set by the researcher. The data analysis method used is to compare the return and risk of the optimal portfolio with the return and risk of individual stocks to show that diversification through the formation of an optimal portfolio using a single index model can minimize investment risk. The results show that portfolio returns tend to be greater than individual stock returns. And portfolio risk is lower than the risk of individual stocks. So that the return and risk from the optimal portfolio that is formed give better performance than the return and risk of individual stocks.